Assessment of Water use Efficiency in the Household Using Cluster Analysis. (2015) - Jorge, Catarina; Vieira, Paula; Rebelo, Margarida; Covas, Dídia
Abstract: Concerns over the efficiency of household water use have been increasing worldwide: water is intensively consumed with high inefficiencies. Detailed methodologies for the assessment of consumers' behaviour that include the level of efficiency comparatively to their peers (i.e., similar socio-demographic characteristics) are needed to increase public awareness and to develop strategies related to the efficient use of water. This paper presents a methodology for evaluating the efficiency of indoor domestic water use based on peer comparison. Peer groups were established through cluster analyses according to their relevant socio-demographic characteristics. Finally, the most efficient consumers were identified and water efficiency levels were determined for individual households.